Efektivitas metode TPS (think-pair-share) berbantu media role-playing card terhadap peningkatan keterampilan berbicara bahasa Jawa materi teks pacelathon - Zahra, Fayza Andini; Insani, Nur Hanifah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Speaking skills in Javanese language learning are often challenging because they require mastery of vocabulary, grammar, and self-confidence. This research aims to determine how effective the Think-Pair-Share (TPS) method using role-playing card media is in improving speaking skills on pacelathon text material. Pretest-posttest control group modeling was used in this quasi-experimental design. There were 68 VIII grade kids in the sample, 34 of whom were in the experimental and control groups. While the control group employed conventionally based methods like lectures and Q&A sessions, the experimental group employed TPS media and techniques. The independent samples t-test and n-gain test were used to evaluate the data. The findings revealed a noteworthy distinction between the two groups (P-value=0.000). The N-Gain obtained by the experimental group was 65.14% (moderately effective), while that of the control group was only 21.84% (ineffective). Thus, the TPS method supported by role-playing card media is effective in improving students' oral proficiency in Javanese. This strategy is recommended to be applied to other learning materials to increase student participation and learning outcomes.